Identifying Critical Success Factors For Social Media Marketing Adoption in Micro and Small Culinary Businesses - Nurqamarani , Adisthy; Priyanto, Agus; Fadilla, Sarah (School of Business, IPB University (SB-IPB), 2024)
Background: With the culinary sector undergoing transformative shifts propelled by technological advancements and the ubiquity of social media, understanding the critical success factors for social media marketing becomes imperative for micro and small businesses. Purpose: This study aims to identify and explore critical success factors for social media marketing adoption in micro and small culinary businesses. Design/methodology/approach: Employing a qualitative approach, the research selected a purposive sample of six Indonesian owners of micro and small culinary businesses, playing pivotal roles in shaping business decisions. Semi-structured interviews conducted via telephone and Zoom Meetings formed the basis for data collection with owners and co-owners of micro and small businesses in the culinary Industry in West Java and East Borneo, Indonesia. The data collection focuses on the critical success factors of social media marketing. Interviews were transcribed and thematically analyzed using a narrative approach.Findings/Result: Five thematic outcomes were noted regarding the critical success factors of social media marketing: interaction, trendiness, persistency, curiosity, and entrepreneurial mindset. The study identifies the